2023
DOI: 10.1002/adma.202308977
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine Combats Drug Resistance in Lung Cancer

Xiuli Zheng,
Xiaohai Song,
Guonian Zhu
et al.

Abstract: Lung cancer is the second most prevalent cancer and the leading cause of cancer‐related death worldwide. Surgery, chemotherapy, molecular targeted therapy, immunotherapy and radiotherapy are currently available as treatment methods. However, drug resistance is a significant factor in the failure of lung cancer treatments. Novel therapeutics have been exploited to address complicated resistance mechanisms of lung cancer and the advancement of nanomedicine is extremely promising in terms of overcoming drug resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 548 publications
0
2
0
Order By: Relevance
“…However, A549 is an exception, exhibiting a very low ΔMedian value. The same phenomenon was also observed when A549 was stained with other dyes, which may be related to low uptake of dyes caused by cell resistance …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…However, A549 is an exception, exhibiting a very low ΔMedian value. The same phenomenon was also observed when A549 was stained with other dyes, which may be related to low uptake of dyes caused by cell resistance …”
Section: Resultssupporting
confidence: 61%
“…The same phenomenon was also observed when A549 was stained with other dyes, which may be related to low uptake of dyes caused by cell resistance. 63 In fluorescence spectroscopy, total cellular RNA was extracted from six cell types, then diluted to the same concentration with Tris-HCl buffer containing K + . After mixing SCY-5 with the RNA solution, the fluorescence of SCY-5 was measured.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent studies have shown that the enrichment of F. nucleatum in colorectal cancer can drive the formation of tumor microenvironment in immunosuppression. 71 As such, eliminating tumor-associated bacteria may be an effective strategy to improve the effect of tumor immunotherapy.…”
Section: Nanomaterials For Bacteria-related Tumor Therapymentioning
confidence: 99%
“…Notably, PEG 2k -PDLLA 2k nanomaterials extend in vivo drug circulation, lower systemic drug exposure, and enable drug-specific delivery [ 33 ]. The resulting nanomicelles enter cells via endocytosis, overcoming the drug-resistant effects of cell membrane P-gp, and passively accumulate in tumor tissues through the enhanced permeability and retention (EPR) effect [ 34 ]. Our preliminary studies affirmed that the triphenyl phosphine (TPP)-modified PEG 2k -PDLLA 2k (termed TPP-PEG 2k -PDLLA 2k , Scheme 1 ) cationic polymeric carrier displayed excellent mitochondrial targeting and prolonged circulation upon systemic administration [ 35 ].…”
Section: Introductionmentioning
confidence: 99%